2007
DOI: 10.1039/b710406e
|View full text |Cite
|
Sign up to set email alerts
|

Clear and present danger? The use of a yeast biosensor to monitor changes in the toxicity of industrial effluents subjected to oxidative colour removal treatments

Abstract: Discharges of coloured effluents into surface waters provide conspicuous evidence of the impact of industry on the environment. The textile industry is an obvious candidate for sources of such discharges. Conventional treatment methods appear to alleviate this situation by removing colour, however the affect on toxicity is less obvious. The objective of this study was to examine the changes in effluent toxicity during the course of two alternative wastewater treatment methods, ozonation and electrochemical oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Catu Lake is a freshwater source that has been used for human consumption and supply, animal consumption, agriculture, industries and leisure activities. Considering that industrial wastes and pollutants are reported as causes of mutagenesis in yeasts (Keenan et al , 2007) and that the occurrence of gene mutation (Feng et al , 2010) may result in antifungal resistance, we believe that the resistance phenomenon observed in these Candida strains is related to anthropic activities developed in the studied area, such as pollution with industrial, agricultural and farming wastes.…”
Section: Discussionmentioning
confidence: 88%
“…Catu Lake is a freshwater source that has been used for human consumption and supply, animal consumption, agriculture, industries and leisure activities. Considering that industrial wastes and pollutants are reported as causes of mutagenesis in yeasts (Keenan et al , 2007) and that the occurrence of gene mutation (Feng et al , 2010) may result in antifungal resistance, we believe that the resistance phenomenon observed in these Candida strains is related to anthropic activities developed in the studied area, such as pollution with industrial, agricultural and farming wastes.…”
Section: Discussionmentioning
confidence: 88%
“…GFP has previously been successfully expressed in P. pastoris using the pPIC3 (Lenassi Zupan et al, 2004) and pPICZB vectors (Hisiger and Jolicoeur, 2005), both of which utilize the AOX1 promoter to drive intracellular gene expression (Sears et al, 1998;Gellissen, 2000). Once expressed, GFP does not usually interfere with cell growth apart from under rare circumstances (Keenan et al, 2007). In this work, GFPH6 gene expression using the pPICKanMX6B vector appears to be the equivalent of pPICZB under the conditions employed in this study.…”
Section: Discussionmentioning
confidence: 89%
“…Crustaceans accumulate pollutants in their tissues, such as hydrocarbons, pesticides and heavy metals (YILMAZ & YILMAZ, 2007), which might increase the azole resistance rate among yeasts from the microbiota, due to the overexpression of effl ux pumps (KEENAN et al, 2007;MÜLLER et al, 2007), as a consequence of the chronic exposure to these chemical compounds. In this context, the use of this prawn as a sentinel for the isolation of Candida spp.…”
Section: Discussionmentioning
confidence: 99%